Meningkatkan Kemampuan Komunikasi matematis Siswa Pada Materi Persamaan Linear Satu Variabel Melalui Penerapan Pendekatan Realistc Mathematic Education (RME) di Kelas VII SMP Negeri Momalia - Pakaya, Astagina Awali; Hulukati, Evi; ,, Majid (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to enhance students’ mathematical communication skills in Linear Equation of One Variable by implementing Realistic Mathematic Education (RME). This study employed Classroom Action Research (CAR) conducted in Class VII at SMP Negeri Momalia during the first semester of the 2024-2025 academic year, with the research subjects comprising 25 students from Class VII-B. Data analysis was performed utilizing a Mathematical Communication Skills Test, teacher activity observations, and student activity observations. The study was conducted through several stages: planning, action, observation, and reflection. The intervention was carried out in two cycles. Based on the findings, teacher activity observations in Cycle I showed a percentage of 61.41%, which enhanced to 89.06% in Cycle II. Similarly, student activity observations increased from 60.41% in Cycle I to 85.41% in Cycle II. The written test result on students’ mathematical communication skill showed that in Cycle I, only 20% of students’ met the Passing Grade (PG), with an average score of 56.2, which enhanced to 84% with an average score of 77.4 in Cycle II. Furthermore, the assessment based on indicators showed an average score of 54.67% in Cycle I, which increased to 77.83% in Cycle II. These findings indicate that implementing Realistic Mathematic Education (RME) effectively enhances the mathematical communication skills of Class VII students at SMP Negeri Momalia.